Complete modal chart of CDWG. Issue 19 (1st September 2018) - Maity, S.; Ghosal, R.; Gangopadhyaya, M.; Gupta, B.
Abstract : Literature survey shows that the modal chart for first 13 modes of cylindrical dielectric waveguide (CDWG) is incomplete. It is found that the 12th mode, i.e. H E M 32 mode has been missed out which exists between H E M 41 and H E M 23 modes. CDWG is reinvestigated here theoretically and the complete modal chart for first 15 modes is given here.